Reliability and concurrent validity of a novel method allowing for in‐shoe measurement of navicular drop - Birgitte H Christensen; Kathrine S Andersen; Kristina S Pedersen; Britt S Bengtsen; Ole Simonsen; Simon L Kappel; Michael S Rathleff (Journal of Foot and Ankle Research, 2014)
Abstract Background Increased navicular drop is associated with increased risk of lower extremity overuse injuries and foot orthoses are often prescribed to reduce navicular drop. For laboratory studies, transparent shoes may be used to monitor the effect of orthoses but no clinically feasible methods exist. We have developed a stretch‐sensor that allows for in‐shoe measurement of navicular drop but the reliability and validity is unknown. The purpose of this study was to investigate: 1) the reliability of the stretch‐sensor for measuring navicular drop, and 2) the concurrent validity of the stretch‐sensor compared to the static navicular drop test. Methods Intra‐ and inter‐rater reliability was tested on 27 participants walking on a treadmill on two separate days. The stretch‐sensor was positioned 20 mm posterior to the tip of the medial malleolus and 20 mm posterior to the navicular tuberosity. The participants walked six minutes on the treadmill before navicular drop was measured. Reliability was quantified by the Intraclass Correlation Coefficient (ICC 2.1) and agreement was quantified by Limits of Agreement (LOA). To assess concurrent validity, static navicular drop was measured with the stretch‐sensor and compared with static navicular drop measured with a ruler on 27 new participants. Linear regression was used to measure concurrent validity. Results The reliability of the stretch‐sensor was acceptable for barefoot measurement (intra‐ and inter‐rater ICC: 0.76‐0.84) but lower for in‐shoe measurement (ICC: 0.65). There was a significant association between static navicular drop measured with the stretch‐sensor compared with a ruler (r = 0.745, p < 0.001). Conclusion This study suggests that the stretch‐sensor has acceptable reliability for dynamic barefoot measurement of navicular drop. Furthermore, the stretch‐sensor shows concurrent validity compared with the static navicular drop test as performed by Brody. This new simple method may hold promise for both clinical assessment and research but more work is needed before the method can be recommended.